2016
DOI: 10.1038/ncomms10893
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of diacylglycerol kinase alpha promotes radiation-induced fibrosis

Abstract: Radiotherapy is a fundamental part of cancer treatment but its use is limited by the onset of late adverse effects in the normal tissue, especially radiation-induced fibrosis. Since the molecular causes for fibrosis are largely unknown, we analyse if epigenetic regulation might explain inter-individual differences in fibrosis risk. DNA methylation profiling of dermal fibroblasts obtained from breast cancer patients prior to irradiation identifies differences associated with fibrosis. One region is characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 67 publications
2
59
0
Order By: Relevance
“…A methylation study of 18 candidate genes found a marginally significant association (P<0.05) between hypermethylation in the promoter region of the XRCC2 gene and late toxicity in cervical cancer patients treated with chemoradiotherapy (129). In the first genome-wide study of differential methylation, hypomethylation of an enhancer region in the gene coding for the signalling kinase DGKA (diacylglycerol kinase alpha) was found to be associated with the risk for developing late reaction (fibrosis) after adjuvant RT in patients treated with breast conserving therapy (130). It was shown that reduced methylation enabled radiation-induced transcription of DGKA and a fibrogenic response.…”
Section: ‘Omics’ Approachesmentioning
confidence: 99%
“…A methylation study of 18 candidate genes found a marginally significant association (P<0.05) between hypermethylation in the promoter region of the XRCC2 gene and late toxicity in cervical cancer patients treated with chemoradiotherapy (129). In the first genome-wide study of differential methylation, hypomethylation of an enhancer region in the gene coding for the signalling kinase DGKA (diacylglycerol kinase alpha) was found to be associated with the risk for developing late reaction (fibrosis) after adjuvant RT in patients treated with breast conserving therapy (130). It was shown that reduced methylation enabled radiation-induced transcription of DGKA and a fibrogenic response.…”
Section: ‘Omics’ Approachesmentioning
confidence: 99%
“…Thus far, all available cancer therapies can carry various side effects and lose effectiveness [5]. With the on-going increase in the number of cancer survivors, the prevention of radiotherapy-associated adverse effects has increasingly become a priority [6] ; [7]. Overall, the gastrointestinal (GI) syndrome is the main toxicity related to abdominal radiotherapy of human cancers [8].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of irradiation on DNA methylation, a key epigenetic mechanism regulating the expression of genetic information could be used to predict response (Miousse et al , 2017). Several studies have highlighted specific epigenetic variants and their impact on late toxicity (Weigel et al , 2016; Weigel et al , 2015). For instance, KDM3B has been shown to have a potential role on histone demethylation and radiosensitivity (Kerns et al , 2016).…”
Section: Radiogenomics Overviewmentioning
confidence: 99%